Continuous-wave-laser surface cleaning of high strength bolts: Analysis of bolt axial force loss. (February 2023) - Wang, Qidi; Kainuma, Shigenobu; Huo, Peng; Zhuang, Shusen
Abstract: This study examined the axial force loss of high-strength bolts after a 3-kW continuous-wave laser (CWL) treatment. Friction connection specimens with M22 high-strength bolts were prepared, and a fixed-angle rotary CWL transmitter with a 26-mm-diameter laser ring and rotating platform was used for nut rotary cleaning of high-strength bolts. Changes in the axial force and temperature of the bolts were monitored during the laser treatment based on the irradiation duration on the nut surface. The experimental results indicated that the minimum and final stable values of the axial force during CWL treatment are affected by the irradiation duration. Multiple rounds of irradiation can reduce the bolt axial force loss for the same total irradiation duration. The 26-mm-diameter laser ring can sufficiently cover the surface of commonly used bolt heads and nuts in bridges, and the local temperature effect does not influence the axial force loss in adjacent bolts. The distribution of the bolt temperature when the CWL treatment the bolt is simulated by an FE model, which proves the overall temperature of the bolt does not exceed 300 °C and remains in a normal working condition when the continuous irradiation duration is less than 45 s. From the relationship between the axial force change and treatment duration, the axial force loss formula was fitted, which can help provide a maintenance plan for M22 bolt cleaning using 3-kW CWL.